Association between unintended pregnancy and maternal antenatal care services use in Ethiopia: analysis of Ethiopian demographic and health survey 2016 - Yalew, Ayalnesh Zemene; Olayemi, Oladapo O.; Yalew, Alemayehu Worku (Frontiers in Medicine, 2023)
Introduction: Unintended pregnancy disproportionately affects women in low and middle –income countries including Ethiopia. Previous studies identified the magnitude and negative health outcome of unintended pregnancy. However, studies that examined the relationship between antenatal care (ANC) utilization and unintended pregnancy are scare. Objective: This study aimed to examine the relationship between unintended pregnancy and ANC utilization in Ethiopia. Methods: The data was taken from Ethiopian Demographic Health Survey (EDHS). The study comprised a weighted sample of 7,271 women who had last live birth and responded to questions on unintended pregnancy and ANC use. The association between unintended pregnancy and ANC uptake were determined using a multilevel logistic regression model adjusted for possible confounders. P-values less than 0.05 were considered significant. Results: Unintended pregnancies accounted for nearly a quarter of all pregnancies (26.5%). After adjusting for confounders, a 33% (AOR: 0.67; 95% CI, 0.57-0.79) lower odds of at least one ANC uptake and a 17% (AOR: 0.83; 95% CI, 0.70- 0.99) lower odds of early ANC booking were found among women who had unintended pregnancy compared to women with intended pregnancy. However, this study founds no association (AOR: 0.88; 95% CI, 0.74, 1.04) between unintended pregnancy and four or more ANC visits. Conclusion: Use of at least one ANC and ANC booking before 12 weeks were found less likely among women with unintended pregnancy compared to women with intended pregnancy. Policies and programs designed to intervene barriers to early initiation and use of ANC should consider unintended pregnancy.